An experimental point of view on hydration/solvation in halophilic proteins - Talon, Romain; Coquelle, Nicolas; Madern, Dominique; Girard, Eric (Frontiers in Microbiology, 2014)
Protein-solvent interactions govern the behaviour of proteins isolated from extreme halophiles. In this work, we compared the solvent envelopes of two orthologous tetrameric malate dehydrogenases from halophilic and non-halophilic bacteria. The crystal structure of the malate dehydrogenase from the non-halophilic bacterium Chloroflexus aurantiacus (Ca MalDH) solved, de novo, at 1.7 Å resolution exhibits numerous water molecules in its solvation shell. We observed that a large number of these water molecules are arranged in pentagonal polygons in the first hydration shell of Ca MalDH. Some of them are clustered in large networks, which cover non-polar amino acid surface. The crystal structure of malate dehydrogenase from the extreme halophilic bacterium Salinibacter ruber (Sr) solved at 1.55 Å resolution shows that its surface is strongly enriched in acidic amino acids. The structural comparison of these two models is the first direct observation of the relative impact of acidic surface enrichment on the water structure organisation between a halophilic protein and its non-adapted counterpart. The data show that surface acidic amino acids disrupt pentagonal water networks in the hydration shell. These crystallographic observations are discussed with respect to halophilic protein behaviour in solution